Answer:
C: .27
Step-by-step explanation:
Add the numbers 20, 11, 14, 30
20 + 11 + 14 + 30 = 75
Divide by what is the time the spinner landed on the letter A by the total
20/75 = .26666667
Round the number to the nearest hundredth and you get
.27
We can say that a relationship between two variables is a function if, for every input, we get one and only one unique output. If we want to talk about y as a function of x in this problem, we want to make sure that every x has only one y associated with it. We can do this by solving our equation for x and seeing whether we can have more than one y that satisfies that equation. Here, I'll do the algebra and briefly explain my steps:
Multiply either side by x to cancel the denominator in 1/x:
Add 5x to either side to collect all of the x terms on one side, and subtract 1 to get all of the constants on one side:
Factor an x out of the left side of the equation:
Divide either side by 3y + 5 to get the x by itself:
For every x we pick, only one y can satisfy the above equation, so we can say that yes, is a function.
Answer:
10/5
Step-by-step explanation:
Because 10 is half of 5 and they are asking what will make this statement true 1/2 is half too
Answer: Either 6 or 7
Step-by-step explanation:
Common denominator is 10 so the equation is
5/10 < /10 < 8/10
Select all that apply
(0,6)
(-1,4)
(-1,-4)
(3,12)
Question 2:
Which ordered pairs are a solution to the equation y=4-2x
Select all that apply
(-1,2)
(0,4)
(-1,6)
(1,6)
Answer:
1.
(0,6)
(-1,6)
(3,12)
2.
(0,4)
(-1,6)
Step-by-step explanation:
The rule for the first question is y = 2x + 6
We can substitute the numbers for each equation.
6 = 2(0) + 6
6 = 6
So (0,6) is correct.
4 = 2(-1) + 6
4 = 4
So (-1,4) is correct as well.
-4 = 2(-1) + 6
-4 ≠ 4
(-1,-4) is incorrect.
12 = 2(3) + 6
12 = 12
So this answer is correct as well.
The second question‘s rule is that y = 4 - 2x. So we can substitute the numbers.
2 = 4 - 2(-1)
2 ≠ 6
This is incorrect.
4 = 4 - 2(0)
4 = 4
This answer is correct.
6 = 4 - 2(-1)
6 = 6
This answer is correct as well.
6 = 4 - 2(1)
6 ≠ 2
This answer is incorrect as well.
Dependent variable
Ordered pairs
Like terms